Tumor Uptake of Triazine Dendrimers Decorated with Four, Sixteen, and Sixty-Four PSMA-Targeted Ligands: Passive versus Active Tumor Targeting - Lim, Jongdoo (Biomolecules, 2019)
Various glutamate urea ligands have displayed high affinities to prostate specific membrane antigen (PSMA), which is highly overexpressed in prostate and other cancer sites. The multivalent versions of small PSMA-targeted molecules are known to be even more efficiently bound to the receptor. Here, we employ a well-known urea-based ligand, 2-[3-(1,3-dicarboxypropyl)-ureido] pentanedioic acid (DUPA) and triazine dendrimers in order to study the effect of molecular size on multivalent targeting in prostate cancer. The synthetic route starts with the preparation of a dichlorotriazine bearing DUPA in 67% overall yield over five steps. This dichlorotriazine reacts with G1, G3, and G5 triazine dendrimers bearing a 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid (DOTA) group for (64)Cu-labeling at the core to afford poly(monochlorotriazine) intermediates. Addition of 4-aminomethylpiperidine (4-AMP) and the following deprotection produce the target compounds, G1-(DUPA)(4), G3-(DUPA)(16), and G5-(DUPA)(64). These targets include 4/16/64 DUPA groups on the surface and a DOTA group at the core, respectively. In vitro cell assay using PC3-PIP (PSMA positive) and PC3-FLU (PSMA negative) cells reveals that G1-(DUPA)(4) has the highest PC3-PIP to PC3-FLU uptake ratio (10-fold) through the PSMA-mediated specific uptake. While G5-(DUPA)(64) displayed approximately 12 times higher binding affinity (IC(50) 23.6 nM) to PC3-PIP cells than G1-(DUPA)(4) (IC(50) 282.3 nM) as evaluated in a competitive binding assay, the G5 dendrimer also showed high non-specific binding to PC3-FLU cells. In vivo uptake of the (64)Cu-labeled dendrimers was also evaluated in severe combined inmmunodeficient (SCID) mice bearing PC3-PIP and PC3-FLU xenografts on each shoulder, respectively. Interestingly, quantitative imaging analysis of positron emission tomograph (PET) displayed the lowest tumor uptake in PC3-PIP cells for the midsize dendrimer G3-(DUPA)(16) (19.4 kDa) (0.66 ± 0.15%ID/g at 1 h. p.i., 0.64 ± 0.11%ID/g at 4 h. p.i., and 0.67 ± 0.08%ID/g at 24 h. p.i.). Through the specific binding of G1-(DUPA)(4) to PSMA, the smallest dendrimer (5.1 kDa) demonstrated the highest PC3-PIP to muscle and PC3-PIP to PC3-FLU uptake ratios (17.7 ± 5.5 and 6.7 ± 3.0 at 4 h p.i., respectively). In addition, the enhanced permeability and retention (EPR) effect appeared to be an overwhelming factor for tumor uptake of the largest dendrimer G5-(DUPA)(64) as the uptake was at a similar level irrelevant to the PSMA expression.